Differentiated Instruction for an Enhanced Students’Academic Performance in Science 10 (PHYSICS) - Toledo, Flordelyn L. (Future Science / FSH-PH Publications, 2023)
The study aimed to determine the effectiveness of Differentiated Instruction strategy using selected Multiple Intelligences activities on the students’ performance in Science 10 (Physics). The researcher employed quasi-experimental research and a descriptive method utilizing questionnaires as the principal tool to gather the data. The respondents involved in the study were the One Hundred Twenty (120) Grade 10 Junior High School students of Bagong Nayon II National High School, Antipolo City, during the school year 2022-2023. They were grouped according to their dominant Multiple Intelligence. The study revealed that among the first five dominant multiple intelligences of the students, the majority of the students are more on intrapersonal intelligence rather than the other. This implies that some of the respondents perform more in intrapersonal tasks and skills which would then indicate that teachers should assess each learner's multiple intelligence to know and enhance students' performance in academics. The use of Differentiated Instruction in teaching Science 10 (Physics) greatly improved the performance of the students in terms of their academics. This was shown on the pretest and posttest performance of the students in which their posttest performance increased greatly after the utilization of differentiated instruction in teaching Science 10. It can also be noted that the Intrapersonal Group of students got the highest increase in mean score. The average mean score in the pretest is 19.49 and 35.69 in the posttest with the mean increase of 16.20. This implies that although the students were given different activities, they all performed well. Based on the findings of the study, teachers can use differentiated instruction for the purpose of enhancing the academic performance of the students. This also implies that the prepared activities intended for these groups of students were effective. Therefore, a student-focused approach of teaching fosters an effective learning environment and excellent academic performance.